2020
DOI: 10.1186/s13063-020-04295-1
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of an intelligent monitoring system for household added salt consumption in China based on a real-world study: a randomized controlled trial

Abstract: Background A high intake of salt is a major risk factor for cardiovascular diseases. Despite decades of effort to reduce salt consumption, the salt intake in China is still considerably above the recommended level. Thus, this study aims to design and implement an intelligent household added salt monitoring system (SALTCHECKER) to monitor and control added salt consumption in Chinese households. Methods A randomized controlled trial will be conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…36 However, the salt intake is considerably above the recommended level in China and most dietary sodium intake is from salt added in home cooking. 37 Our finding showed that females with hypertension consumed less salt than males. This may be related to the fact that females have more knowledge of controlling hypertension and pay more attention to healthy diet.…”
Section: Discussionmentioning
confidence: 53%
“…36 However, the salt intake is considerably above the recommended level in China and most dietary sodium intake is from salt added in home cooking. 37 Our finding showed that females with hypertension consumed less salt than males. This may be related to the fact that females have more knowledge of controlling hypertension and pay more attention to healthy diet.…”
Section: Discussionmentioning
confidence: 53%
“…Because computer intelligent monitoring technology has the function of automatic classification of data, it can quickly classify packages in the face of a large number of express packages. e classified package can accurately deliver the express to the buyer, and the delivery time of the express package is also shortened (Xian et al, 2020) [15]. Computer intelligent monitoring technology is also widely used in other fields in China and has brought positive results to various industries, which also makes computer intelligent monitoring technology valued by mankind.…”
Section: Related Workmentioning
confidence: 99%
“…For example, the widespread use of smartphones and social media apps like WeChat make more health-related knowledge and education materials accessible to people regardless of their locations and SES. Another example is that a smart salt jar was developed by a Chinese company to monitor household salt consumption ( 25 ). The system not only provided information on household salt usage but also offered health messages and guidance on managing hypertension.…”
Section: Opportunitiesmentioning
confidence: 99%